Environmental accounting information disclosure and shareholders’ investment decisions in listed oil and gas firms in Nigeria - Chinanu, Emmanuel; Folajimi, Adegbie F (Journal of Social Economics Research, 2024)
This study examines the effect of environmental accounting information disclosure (EAID) on the investment decisions of shareholders of listed oil and gas firms in Nigeria. Expost facto research design was adopted, utilizing secondary data extracted from the annual reports of eight sampled firms for a period of eighteen years from 2005-2022. The study explored panel regression analysis using Random Effect Model with Driscoll-Kraay Standard Errors for Models 1 and 2. The statutory auditors of the sampled firms certified the financial statements, thereby establishing the validity and reliability of the study’s data. The findings revealed that environmental accounting information disclosure exerted a significant effect on market share value in model 1 as well as on market capitalization in model 2. As a result, the study concludes that environmental accounting information disclosure has a significant impact on the investment decisions of shareholders of listed oil and gas firms in Nigeria. In line with the findings, the study recommends that policymakers should ensure enforcement and strict compliance of existing environmental policies and greenhouse and ecological preservation disclosures in oil and gas firms listed in Nigeria.